2022
DOI: 10.1037/trm0000336
|View full text |Cite
|
Sign up to set email alerts
|

“I hate it, it’s ruining my life”: College students’ early academic year experiences during the COVID-19 pandemic.

Abstract: Due to strategies aimed at controlling COVID-19, governments across the world implemented social distancing and stay-at-home measures, which has resulted in isolation and economic crisis (Golberstein et al., 2019). To date, few studies have examined individuals' experiences of COVID-19, but these have mostly been focused on frontline workers and the medical field. The purpose of this study was to determine how COVID-19 has affected collegiate student mental health by assessing their perceived challenges and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
(47 reference statements)
0
18
0
Order By: Relevance
“…University counseling centers quickly pivoted to virtual and distance support models as campuses closed across the country. Despite the pandemic's devastating mental health impact on college students, counseling centers experienced dramatic decreases in the number of students seeking support ( Madrigal & Blevins, 2021, in press ). In fact, only 15% of students who rated their mental health as poor engaged in campus mental health services during the peak of the COVID-19 pandemic ( Ezarik, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…University counseling centers quickly pivoted to virtual and distance support models as campuses closed across the country. Despite the pandemic's devastating mental health impact on college students, counseling centers experienced dramatic decreases in the number of students seeking support ( Madrigal & Blevins, 2021, in press ). In fact, only 15% of students who rated their mental health as poor engaged in campus mental health services during the peak of the COVID-19 pandemic ( Ezarik, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the university context, justice experiences with fellow students and lecturers were examined. Interventions against COVID-19 required universities to adapt teaching 4 , 55 . At the University of Cologne, digital synchronous and asynchronous teaching was offered, which led to contact reduction among students and with lecturers.…”
Section: Discussionmentioning
confidence: 99%
“…The lecturers' justice-related behaviors are also transparent at the digital level through the given rules and norms. However, the experience of fellow student justice was distorted by the lack of social contact 55 .…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, it is possible that the stagnation or decline in teacher self-efficacy in the COVID-19 group was a product of the disruption to their learning caused by the COVID-19 pandemic more generally, rather than the lack of school practicums specifically. For example, research examining the impact of online teaching on university students has found that students perceive themselves as learning less online as compared to face-to-face teaching ( Usher et al, 2021 ), as well as experiencing more negative emotions towards their learning ( Madrigal & Blevins, 2021 ; Usher et al, 2021 ). For student teachers specifically, the removal of practical experiences in schools led to anxiety about how it would impact their own teacher development and ability to graduate ( Kidd & Murray, 2020 ).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%